2018
DOI: 10.1002/hpja.60
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor physical activity for older people—the senior exercise park: Current research, challenges and future directions

Abstract: The inclusion of outdoor equipment for older people in public spaces or urban parks is important and careful consideration needs to be taken by local/public authorities to provide access, amenities and safety for all as well as activities to suit all ages. SO WHAT?: Seniors' exercise parks can be installed in public places and may provide an enjoyable and effective approach to engage older individuals in a more active and healthier lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…Finally, Zhai [20] found that, as long as the destination is attractive, 23.4% of elderly people would visit high-quality parks that are far away from home. All of these studies also indicate that the elderly have stricter requirements and needs in terms of usability [19], accessibility [19], safety [16], comfort [15], and entertainment [20] in parks than younger people.On the whole, much research has been conducted on how urban planners should design suitable parks for the diversified needs of the elderly based on their health conditions [13][14][15], behavioral abilities, and characteristics [7,[13][14][15][16]. However, there is still no research on the spatial difference of the elderly suitability of parks in a single city or in certain kinds of cities.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Finally, Zhai [20] found that, as long as the destination is attractive, 23.4% of elderly people would visit high-quality parks that are far away from home. All of these studies also indicate that the elderly have stricter requirements and needs in terms of usability [19], accessibility [19], safety [16], comfort [15], and entertainment [20] in parks than younger people.On the whole, much research has been conducted on how urban planners should design suitable parks for the diversified needs of the elderly based on their health conditions [13][14][15], behavioral abilities, and characteristics [7,[13][14][15][16]. However, there is still no research on the spatial difference of the elderly suitability of parks in a single city or in certain kinds of cities.…”
mentioning
confidence: 95%
“…Finally, Zhai [20] found that, as long as the destination is attractive, 23.4% of elderly people would visit high-quality parks that are far away from home. All of these studies also indicate that the elderly have stricter requirements and needs in terms of usability [19], accessibility [19], safety [16], comfort [15], and entertainment [20] in parks than younger people.…”
mentioning
confidence: 95%
See 3 more Smart Citations